Avaliação dos macrófagos e das células gliais na dor da carcinogênese oral em ratos - Alves, Luiza Clertiani Vieira (2024)
Orofacial pain impacts the quality of life of patients with head and neck cancer. Research into the molecular mechanisms of orofacial pain often focuses on understanding the role of neuronal cells in the painful process; however, glial cells are notably recognized for their contribution to the development and/or maintenance of abnormal neuronal excitability, including nociceptive transmission. While these cells do not generate electrical impulses, they can release various neurotransmitters and growth factors that may influence neuronal activity. The role of macrophages in the immune response is well-known, and their interactions with cancer cells can have either pro- or antitumor effects, depending on their activation state. Thus, the aim of this study was to investigate the activation state of macrophages during the development of oral carcinogenesis and the role of glial cells in the trigeminal nociceptive pathway in the establishment of pain in oral carcinogenesis induced by 4-nitroquinoline 1-oxide (4-NQO) in Wistar rats. Material previously collected from paraffin-embedded blocks of tongue samples at 0, 8, 12, 16, and 20 weeks of 4-NQO administration, as well as cryoprotected trigeminal ganglion (GT) and caudal subnucleus of the trigeminal nerve (Sp5C) from animals subjected to oral carcinogenesis induction for 16 and 20 weeks, was utilized. Tongue samples underwent immunohistochemistry for Iba-1 and CD-206, and immunofluorescence was performed to analyze the immunoreactivity of p-p38, nitrotyrosine, and glutamine synthetase in GT and Iba-1 in the Sp5C region. Microglial morphology was also assessed in the Sp5C region. A significant increase in Iba-1 immunoreactivity was observed in the lamina propria region of the tongue in the 4-NQO 16 and 20-week groups, while no CD-206 immunoreactivity was observed in the evaluated groups. There was a significant increase in nitrotyrosine and p-p38 immunoreactivity in the group receiving the carcinogen for 20 weeks compared to other groups, and a significant increase in the number of satellite cells/neuron in the groups receiving 4-NQO, with a significantly higher number in the 4-NQO 20-week group. A significant increase in Iba-1 immunoreactivity in the Sp5c region was also observed in groups receiving 4-NQO compared to the Control. In the analysis of microglial morphology, a significant increase in the number and length of microglial branches was noted in groups receiving 4-NQO. However, animals receiving 4-NQO for 20 weeks showed a significant reduction in these parameters, presenting a more amoeboid morphology compared to the 4-NQO 16-week group, indicating an activated state. In conclusion, during the development of oral carcinogenesis, there is an increase in M1 macrophages, and glial cells participate in this process, contributing to the establishment of the inflammatory and neuropathic characteristics present in oral cancer pain.